Primary thyroid-like low-grade nasopharyngeal papillary adenocarcinoma: A case report and literature review. Issue 47 (November 2017) - Zhang, Wan-Lin; Ma, Shuang; Havrilla, Lauren; Cai, Lin; Yu, Cheng-Qian; Shen, Shuai; Xu, Hong-Tao; Wang, Liang; Yu, Juan-Han; Lin, Xu-Yong; Wang, Endi; Yang, Lian-He
Abstract: Rationale: Primary thyroid-like low-grade nasopharyngeal papillary adenocarcinoma (TL-LGNPPA) is an extremely rare malignant nasopharyngeal tumor with features resembling papillary thyroid carcinoma including nuclear positive expression of thyroid transcription factor-1 (TTF-1). Patient concerns: A 64-year-old male presented with nasal bleeding and a foreign body sensation of the nasopharynx. Laryngoscopy revealed a 2.0-cm broad-based mass with a smooth surface on the posterior wall of the nasopharynx. A biopsy was obtained. Diagnoses: Histopathologic examination demonstrated tumor cells arranged in both papillary and glandular architecture. The tumor cells express nuclear immunoreactivity for TTF-1. The diagnosis of TL-LGNPPA was made. Interventions: After the patient was diagnosed with TL-LGNPPA, he underwent complete surgical resection. Outcomes: There was no recurrence or evidence of metastatic disease at the 12-month follow-up. Lessons: TL-LGNPPA is easy to misdiagnose as metastatic papillary thyroid carcinoma or other relative primary adenocarcinomas. It is important to have a broad differential diagnosis and know the key features of each entity because the prognosis and clinical treatment of each may differ.